2019
DOI: 10.1177/1420326x19876071
|View full text |Cite
|
Sign up to set email alerts
|

Study on subjective sensation and physiological reaction with high physical activity influenced by air temperature of stadium

Abstract: As the main venue for sports training and competition, the thermal environment of a stadium directly could affect the comfort and health of a moving body and sports performance. In this study, the quantitative relationship between ambient temperature and subjective sensation evaluation was established by monitoring the actual thermal sensation evaluation, fatigue sensation cognition and physiological response with high physical activity, under different conditions of ambient temperature. The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The degree of perceived human thermal sensation levels could be influenced by the type of physical activity, whether sedentary or active 150,151 . Sensitivity to thermal sensation or comfort is highly dependent on the amount of internal heat stress generated by the muscle, which is also partly controlled by the level of physical activity 152 .…”
Section: Impact Of Pcm‐embedded Vest On Personal Thermal Comfortmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of perceived human thermal sensation levels could be influenced by the type of physical activity, whether sedentary or active 150,151 . Sensitivity to thermal sensation or comfort is highly dependent on the amount of internal heat stress generated by the muscle, which is also partly controlled by the level of physical activity 152 .…”
Section: Impact Of Pcm‐embedded Vest On Personal Thermal Comfortmentioning
confidence: 99%
“…The degree of perceived human thermal sensation levels could be influenced by the type of physical activity, whether sedentary or active. 150,151 Sensitivity to thermal sensation or comfort is highly dependent on the amount of internal heat stress generated by the muscle, which is also partly controlled by the level of physical activity. 152 This implies that it is important to evaluate how the PCM vest affects the human thermal comfort level under a sedentary lifestyle based on the summarised studies compiled in Table 3.…”
Section: Personal Cooling Effect Of Pcm Under Sedentary Activitymentioning
confidence: 99%
“…Very few studies focused on the thermal sensation of sports players in sports buildings undertaking sports and exercises. [16][17][18] However, thermal sensation study in the sport environment is necessary to pursue health and wellbeing and to attain a high quality of life for human subjects. Based on this background, this study undertakes a research into the thermal sensation of basketball players in gymnasium during sport activity such as a basketball game.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 25 conducted experimental research on strenuous exercise (3.5-5.0 met) and indicated that the heart rate and wrist skin temperature can be utilized for evaluating the thermal sensation. Xiao et al 18 monitored the subjective sensation and physiology with high physical activity under different ambient temperature and found significant effect of ambient temperature on objective response. Research from Henriques et al, 26 Zhu et al 27 and Zhai et al 28 analysed the relationship between thermal comfort and different levels of intensity.…”
Section: Introductionmentioning
confidence: 99%